Evolution of vertebrate respiratory central rhythm generators - Milsom, W. K.; Kinkead, R.; Hedrick, M. S.; Gilmour, K.; Perry, S.; Gargaglioni, L. [UNESP]; Wang, T. (Elsevier, 2022)
Tracing the evolution of the central rhythm generators associated with ventilation in vertebrates is hindered by a lack of information surrounding key transitions. To begin with, central rhythm generation has been studied in detail in only a few species from four vertebrate groups, lamprey, anuran amphibians, turtles, and mammals (primarily rodents). Secondly, there is a lack of information regarding the transition from water breathing fish to air breathing amniotes (reptiles, birds, and mammals). Specifically, the respiratory rhythm generators of fish appear to be single oscillators capable of generating both phases of the respiratory cycle (expansion and compression) and projecting to motoneurons in cranial nerves innervating bucco-pharyngeal muscles. In the amniotes we find oscillators capable of independently generating separate phases of the respiratory cycle (expiration and inspiration) and projecting to pre-motoneurons in the ventrolateral medulla that in turn project to spinal motoneurons innervating thoracic and abdominal muscles (reptiles, birds, and mammals). Studies of the one group of amphibians that lie at this transition (the anurans), raise intriguing possibilities but, for a variety of reasons that we explore, also raise unanswered questions. In this review we summarize what is known about the rhythm generating circuits associated with breathing that arise from the different rhombomeric segments in each of the different vertebrate classes. Assuming oscillating circuits form in every pair of rhombomeres in every vertebrate during development, we trace what appears to be the evolutionary fate of each and highlight the questions that remain to be answered to properly understand the evolutionary transitions in vertebrate central respiratory rhythm generation.
Keywords: Breathing in vertebrates; Central respiratory rhythm generation; Control of breathing; Evolution